Penerapan Strategi Pembelajaran Kontekstual Pada Pembelajaran Fiqih Dengan Media Pembelajaran Audio Visual Di Madrasah Tsanawiyah (MTs) - Thahir, Thahir; Suhaimi, Ach. (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
This research is motivated by the application of contextual learning strategies using audio-visual media in a learning process in the classroom. The learning process in the classroom is a very important thing that a teacher needs to pay attention to. The learning process must be equipped with strategies and media as tools to help the learning process run smoothly in the classroom. Contextual strategies and audio-visual media are one of the strategies and media chosen by a teacher that can be applied and used in the learning process in the classroom with the aim of making the learning process run smoothly and achieving the goals desired by a teacher and students. The existence of strategies and media can make it easier for a teacher to convey learning material well and can also be easily understood by students.